2007
DOI: 10.1007/s10661-007-9833-9
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the quality of various bottled mineral water marketed in Turkey

Abstract: Fifteen bottled mineral waters purchased at random all over Turkey were analyzed for their chemical composition by OPTIMA-2000 ICP-AES Perkin Elmer techniques. Results show a wide spread in the chemical specification of these mineral waters, with differences in chemical composition observed in the regions being due to the geological environment and the majority of bottled mineral waters exceeding the pH limit of Turkish drinking water standards. When the concentrations of elements are evaluated, it can readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…The analyses were done by using American Public Health Association (APHA 18 th edition 1992) guidelines [19]. Analyses included physical and aggregate properties such as colour, odour, turbidity, total dissolved solids, total alkalinity and total hardness; major non-metallic, inorganic constituents such as pH, chloride, fluoride, and sulphate; major and trace metals including sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), zinc (Zn), arsenic (As), cadmium (Cd), chromium (Cr), cobalt (Co), copper (Cu), lead (Pb), manganese (Mn), molybdenum (B), nickel In this study, the mean value of lead was found to be more than the FDA standard value, which was in agreement with findings of the study done by Salam et al, [24] Contrary results were found in the studies done by Soylak M et al, [25], Akpoborie and Ehwarimo [26], Babaji et al, [27], Saeed et al, [28] and Baba et al, [20], in which the lead levels were lesser than the standard values. There was only a marginal increase in the mean value of copper in bottled water as compared to the Indian standards.…”
Section: Samplingsupporting
confidence: 91%
“…The analyses were done by using American Public Health Association (APHA 18 th edition 1992) guidelines [19]. Analyses included physical and aggregate properties such as colour, odour, turbidity, total dissolved solids, total alkalinity and total hardness; major non-metallic, inorganic constituents such as pH, chloride, fluoride, and sulphate; major and trace metals including sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), zinc (Zn), arsenic (As), cadmium (Cd), chromium (Cr), cobalt (Co), copper (Cu), lead (Pb), manganese (Mn), molybdenum (B), nickel In this study, the mean value of lead was found to be more than the FDA standard value, which was in agreement with findings of the study done by Salam et al, [24] Contrary results were found in the studies done by Soylak M et al, [25], Akpoborie and Ehwarimo [26], Babaji et al, [27], Saeed et al, [28] and Baba et al, [20], in which the lead levels were lesser than the standard values. There was only a marginal increase in the mean value of copper in bottled water as compared to the Indian standards.…”
Section: Samplingsupporting
confidence: 91%
“…In contrast, literature indicates that in other countries the levels of these essential elements in some bottled water are either lower or higher than the recommended level of the countries' standard limits (Ikem et al 2002;Pip 2002;Mahajan et al 2006;Baba et al 2008). Since the levels of the study research elements are within the range, therefore, there should be no serious concern regarding the health-effects due to these elements.…”
Section: Discussionmentioning
confidence: 97%
“…Another negative effect is injector blocking due to carbon deposition from incomplete oxidation of the organic matrix. The most severe non-spectroscopic interference in ICP-MS is the space charge effect where the ion beam is disturbed in the path through the ion optics and mass spectrometer (Anthemidis et al 2005;Alhas et al 2009;Saint Pierre et al 2004;Kahen et al 2003;Baba et al 2008).…”
Section: Detection Techniquesmentioning
confidence: 99%